Regional distribution of foreign manufacturing investment in Spain. Do agglomeration economies matter? - Angels Pelegrín Solé (European Regional Science Association (ERSA), 2004)
The objective of this paper is to examine the nature and determinants of the regional distribution of FDI within Spain with special emphasis in agglomeration factors. Although the paper focuses in the manufacturing investment, considered a key factor in the economic transformation happened during the last 35 years, and traditionally the large part of FDI until the mid of eighties, the analysis distinguish between total FDI case and manufacturing FDI case. The paper is of interest for two main reasons: first this study introduces agglomeration and urbanization variables to test if they are decisive location factors. As it is showed in the part of description of the variables, there are very few studies of location determinants that consider new economic geography variables. In second tem, there are very few studies of location determinants of FDI in Spain, and even fewer that focus in regional areas. The precedent of this paper is another previous study, where the traditional cost and market determinants were empirically tested, a descriptive part of the work showed a high geographical concentration, so one possible explication could be that agglomeration and urbanization economies were decisive location factors. This study introduces some agglomeration and urbanization variables to test if they are decisive location factors in Spanish regions, distinguishing total FDI case and manufacturing FDI case. The article is divided into five further sections. The next section examines the location determinants of FDI and reviews the existing literature in regional/state location factors. The second section provides details on the database and the econometric methodology. In the forth section the empirical results are discussed. The final section offers a summary and concluding remarks.
Keywords: 330